Evaluasi Penerimaan Ukm Terhadap Sistem Informasi Akuntansi - Anita Wijayanti (STMIK Sinar Nusantara, 2011)
The role of SMEs in the economy of a country, including Indonesia, can not be underestimated. Although the role of SMEs is very strategic, but the tight competition, has put SMEs in unfavorable position. Most of the SMEs doing business with traditional ways, including in the accounting process conducted by the company. Accounting Information Systems, which materialized due to advances in information technology (IT), comes with new opportunities that SMEs can overcome some problems, but so far untapped AIS applications required of SMEs, it was found by analyzing the effect of variable ease of use and usefulness (Technology Acceptance Model (TAM)), as well as content, accurat, format, ease and timeliness (End User Computing Satisfaction (EUCS)) against the acceptance of AIS by SMEs . Based on interactive analysis of linear regression statistical test hasi can be arranged SIA model for SMEs. Based on the analysis conducted in this study, it can be concluded that factors in the Technology Acceptance Model (TAM) and End User Computing Satisfaction (EUCS) affect the acceptance of accounting information system by SMEs in Cluster Laweyan Kampung Batik Surakarta, so the SIA penyususna for SMEs in Cluster Laweyan Kampung Batik Surakarta, need memperhatikanvariabel-existing variables in the model of acceptance of the Technology Acceptance Models (TAM) and End User Computing Satisfaction (EUCS)Key words : SIA,TAM, EUCS